Mannan Enhances IL-12 Production by Increasing Bacterial Uptake and Endosomal Degradation in L. acidophilus and S. aureus Stimulated Dendritic Cells - Mathiesen, Ronja; Eld, Helene M. S.; Sørensen, Juliane; Fuglsang, Eva; Lund, Lisbeth Drozd; Taverniti, Valentina; Frøkiær, Hanne (Frontiers in Immunology, 2019)
The mannose receptor (MR) is a C-type lectin involved in endocytosis with a poorly defined ability to modulate cellular activation. We investigated the effect of mannan treatment prior to stimulation of murine bone marrow derived dendritic cells with the Gram-positive bacteria Lactobacillus acidophilus NCFM (L. acidophilus) on the induction of Interleukin (IL)-12. Mannan enhanced the IL-12 production induced by L. acidophilus in a dose dependent manner (up to 230% enhancement) and showed the same effect on Staphylococcus aureus induced IL-12 but the opposite effect was seen on Escherichia coli stimulated cells. Also the expression of Ifnb encoding interferon (Ifn)- induced by the Gram-positive bacteria was increased by mannan. Addition of mannan but not of bacteria led to endocytosis of MR. Addition of mannan prior to L. acidophilus or S. aureus resulted in increased endocytosis of bacteria, a faster killing of endocytosed bacteria, and increased reactive oxygen species production. Expression of signaling lymphocytic activation molecule (SLAMF)1 shown previously to be involved in the facilitation of endosomal degradation was upregulated by mannan but not by L. acidophilus and S. aureus. The IL-12 enhancement by mannan but not the IL-12 induced by the bacteria was abrogated by addition of inhibitors of clathrin coated pits (chlorpromazine and monodansylcadeverine). Addition of acid sphingomyelinase, a facilitator of ceramide raft formation, prior to addition of L. acidophilus enhanced the IL-12 production and the endocytosis of bacteria. In summary, our results show that mannan increases the IL-12 production induced by some Gram-positive bacteria through MR-endocytosis, which increases bacterial endocytosis and endosomal killing. The differential effect of MR activation on the IL-12 production induced by Gram-positive and Gram-negative bacteria may influence the immune response towards allergens and other glycoproteins.